Health Literacy and How Rural Communities Understand Hypertension Information in Kabale, Uganda - Rob Freer (Adult Education Research Conference, 2015)
This research examines health literacy and how rural communities understand hypertension information in Kabale, Uganda. Commonly defined as an individual’s ability to access, understand, and use information to promote and maintain positive health and well-being, health literacy and hypertension has yet to be problematized within an African context.
Keywords: health; literacy; hypertension; Africa